Ethics in Action: Nurturing Green Behaviors in the Workplace Through Corporate Environmental Ethics and Supervisor Ethical Leadership - Saleem, Shaham (Journal of business ethics, 2026)
In today’s dynamic organizational landscape, promoting environmentally responsible behaviors among employees is paramount for sustainable business practices. However, the mechanisms through which corporate environmental ethics (CEE) influence these behaviors remain underexplored. This study addresses this gap by examining the direct and mediated (via environmental passion) pathways through which CEE promotes the required green behavior (RGB). Specifically, this study investigated the moderating influence of supervisor ethical leadership on the relationship between CEE and employees’ RGB. In addition, this study tested the spillover effect of RGB on employees’ proactive green behavior with the boundary condition of perceived distributive justice to facilitate the positive spillover effect between them. By conducting two multiwave and multisource studies, this study confirms the validity of its hypotheses. These findings contribute to the research on CEE’s essential but primarily neglected function in shaping workers’ green habits and spillover effects within the workplace.